Aircraft hydraulic power system diagnostic, prognostics and health management - Wang, Jian (Cranfield University, 2012)
This Individual Research Project (IRP) is the extension research to the group design project (GDP) work which the author has participated in his Msc programme. The GDP objective is to complete the conceptual design of a 200-seat, flying wing civil airliner—FW-11. The next generation aircraft design demands higher reliability, safety and maintainability. With the development of the vehicle hydraulic system technology, the equipment and systems become more and more complex, their reliability and maintenance become more difficult for designers, manufacturers and customers. To improve the mission reliability and reduce life cycle cost, there is strong demand for the application of health management technology into airframe system design. In this research, the author introduced diagnostic, prognostic and health management (DPHM) concept into the aircraft hydraulic power system development. As a brand new technology, it is a challenge to apply the DPHM techniques to on-board system. Firstly, an assumed hydraulic power system was designed for FW-11 by the author and used as the case in his IRP research. Then the crucial components and key parameters needed to be monitored were obtained based on Function Hazard Analysis and Failure Modes Effects Analysis of this system. The writer compared a few diagnostic and prognostic methods in detail, and then selected suitable ones for a hydraulic power system. A diagnostic process was applied to the hydraulic power system using a Case-based reasoning (CBR) approach, whilst a hybrid prognostic method was suggested for the system. After that, a diagnostic, prognostic and health management (DPHM) architecture of the hydraulic power system was designed at system level based on the diagnostic and prognostic research. The whole research work provided a general and practical instruction for hydraulic system design by means of DPHM application.
Keywords: Hydraulic; FMEA; CBR; DPHM; diagnostic; prognostic